Gentiana sasidharanii (Gentianaceae), a new species from Western Ghats, India - Prabhukumar, Konickal Mambetta; Sunil, Chandrasseril Narayanan; Sreejith, Chittiyath Madhavan; Kumar, Vannaratta Veettil Naveen; Balachandran, Indira (Phytotaxa, 2020)
Gentiana sasidharanii, a new species of Gentianaceae, from Western Ghats of Kerala, India, is here described and illustrated. Species distribution, phenology and colour photographs of the new species are provided. A comparative table of the new species with G. kurumba, and a key to allied species are also presented.